PENGARUH LITERASI KEUANGAN TERHADAP PERILAKU KONSUMTIF MAHASISWA - Meilani Al Rahmatia, Sinar Cahyani, Septi Ramdayanti, Cici Awalia (PT Wahana Global Education, 2025)
This study aims to analyze the influence of financial literacy on student consumer behavior. The phenomenon of increasing consumer behavior among students is a serious concern because it can have an impact on their personal financial condition. The research method used is quantitative with a survey approach to students from the Sumbawa University of Technology. The instrument used is a questionnaire that measures the level of financial literacy and the tendency of consumer behavior of respondents. The results of the regression analysis show that financial literacy has a negative and significant effect on student consumer behavior. This means that the higher the level of financial literacy, the lower the level of student consumer behavior. This finding indicates the importance of early financial education to form wiser consumption behavior. This study is expected to be a reference for educational institutions in designing financial literacy programs for students.